2005
DOI: 10.1080/10408360500295154
|View full text |Cite
|
Sign up to set email alerts
|

Cytokines in the Differentiation Therapy of Leukemia: From Laboratory Investigations to Clinical Applications

Abstract: Differentiation therapy of leukemia is the treatment of leukemia cells with biological or chemical agents that induce the terminal differentiation of the cancer cells. It is regarded as a novel and targeted approach to leukemia treatment, based on our better understanding of the hematopoietic process and the mechanisms of its deregulation during leukemogenesis. Clinically, differentiation therapy has been most successful in acute promyelocytic leukemia using all-trans-retinoic acid as the inducer, either alone… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 183 publications
0
9
0
Order By: Relevance
“…IL-6 was defined as a crucial factor for tumor survival and immune evasion, i.e., via induced secretion of IL-10 by regulatory T cells, which effectively suppresses adaptive immune responses towards tumor antigens [33] and induces proliferation of immature myeloid cells [34]. The combination of IL-6 and its inducers TNF-α and IL-1β [35] promotes tumor growth and survival in cancer patients through maintenance of chronic inflammation and induction of a tumor-supporting microenvironment [19, 36].…”
Section: Discussionmentioning
confidence: 99%
“…IL-6 was defined as a crucial factor for tumor survival and immune evasion, i.e., via induced secretion of IL-10 by regulatory T cells, which effectively suppresses adaptive immune responses towards tumor antigens [33] and induces proliferation of immature myeloid cells [34]. The combination of IL-6 and its inducers TNF-α and IL-1β [35] promotes tumor growth and survival in cancer patients through maintenance of chronic inflammation and induction of a tumor-supporting microenvironment [19, 36].…”
Section: Discussionmentioning
confidence: 99%
“…111 Some of the hematopoietic leukemia cell lines of myeloid origin such as K562, U937, HL-60, CS-1, KG-1, MUTZ-3, or ex vivo AML or chronic myeloid leukemia (CML) blasts were modestly permissive to induction of in vitro differentiation by EPO, G-CSF, GM-CSF, IL-4, IL-6, SCF, or synergistic combinations of several cytokines. [111][112][113][114][115] Molecular mechanisms of cytokineinduced leukemic differentiation were also elucidated. Several prominent proto-oncogenes such as c-myb, c-myc, c-fos, and Ets family transcription factors such as ets-1, fli-1, and TEL2 were found to be differentially regulated upon cytokine-induced differentiation of leukemic cells.…”
Section: Cytokinesmentioning
confidence: 99%
“…Active growth of tumor cells can also be attenuated by induction of terminal differentiation and this approach has been developed as one of the strategies in cancer treatment [96]. Previously, Zeng and Tu showed that Rh 2 -treated hepatocarcinoma (SMMC-7721) cells exhibited the morphological characteristics of mature cells.…”
Section: Pharmacological Actions Of Ginsenosidesmentioning
confidence: 99%